Efektivitas penerapan check list pemantauan post-anesthesia care unit (PACU) dalam menurunkan insiden komplikasi pasca anestesi - Mukhamad Ikhsan; Made Suandika; Martyarini Budi (THE JOURNAL OF Nursing Management Issues, 2025)
Background: Post-general anesthesia complications remain a significant issue in perioperative care and can be prevented through systematic monitoring in the Post-Anesthesia Care Unit (PACU). Purpose: To analyze the effectiveness of implementing a PACU monitoring checklist in reducing the incidence of post-geneal anesthesia complications at Merauke Regional General Hospital. Method: A quantitative research with an analytical observational approach and a cross-sectional study design. The study sample consisted of 128 patients who underwent general anesthesia at Merauke Regional General Hospital, selected using purposive sampling. Data were collected through observation and documentation using the PACU checklist to assess the completeness of monitoring, as well as an observation form for general anesthesia complications. Data analysis used the Chi-Square test with a significance level of p < 0.05. Results: The results showed that the majority of checklist implementation fell into the “complete” category (67.2%). Most patients did not experience post-general anesthesia complications (64.1%); however, complications such as pain, postoperative nausea and vomiting (PONV), hypoxia, hemodynamic disturbances, shivering, and decreased consciousness were still observed. There was a significant association between the implementation of the PACU checklist and the incidence of post-general anesthesia complications (p = 0.000), where the complete implementation of the checklist was proven to be more effective in reducing the incidence of complications. Conclusion: Implementation of the PACU monitoring checklist is associated with and effective in reducing the incidence of post-general anesthesia complications in patients at Merauke Regional General Hospital.   Keywords: General Anesthesia; PACU checklist; Patient Safety; Post-Anesthesia Complications.   Pendahuluan: Komplikasi pasca anestesi umum masih menjadi masalah penting dalam pelayanan perioperatif dan dapat dicegah melalui pemantauan yang sistematis di Post-Anesthesia Care Unit (PACU). Tujuan: Untuk menganalisis efektivitas penerapan check list pemantauan PACU terhadap penurunan insiden komplikasi pasca anestesi umum di Rumah Sakit Umum Daerah (RSUD) Merauke. Metode: Penelitian kuantitatif dengan pendekatan observasional analitik dan rancangan cross sectional study. Sampel penelitian berjumlah 128 pasien yang menjalani anestesi umum di RSUD Merauke yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui observasi dan studi dokumentasi menggunakan lembar check list PACU untuk menilai tingkat kelengkapan pemantauan serta lembar observasi komplikasi pasca anestesi umum. Analisis data menggunakan uji Chi-Square dengan tingkat kemaknaan p < 0,05. Hasil: Sebagian besar penerapan check list berada pada kategori lengkap (67.2%). Sebagian besar pasien tidak mengalami komplikasi pasca anestesi umum (64.1%), namun masih ditemukan komplikasi seperti nyeri, postoperative nausea and vomiting (PONV), hipoksia, gangguan hemodinamik, shivering, dan penurunan kesadaran. Simpulan: Terdapat hubungan yang signifikan antara penerapan check list PACU dengan kejadian komplikasi pasca anestesi umum (p = 0,000), dimana penerapan check list yang lengkap terbukti lebih efektif dalam menurunkan insiden komplikasi. Disimpulkan bahwa penerapan check list pemantauan PACU berhubungan dan efektif dalam menurunkan kejadian komplikasi pasca anestesi umum pada pasien di RSUD Merauke. Kata kunci: Anestesi Umum; Check List PACU; Keselamatan Pasien; Komplikasi Pasca Anestesi.